Rearrangeable-Nonblocking Five-Port Silicon Optical Switch for 2-D-Mesh Network on Chip - Ting Zhou; Hao Jia; Jincheng Dai; Shanglin Yang; Lei Zhang; Xin Fu; Lin Yang (IEEE Photonics Journal, 2018)
We propose and experimentally demonstrate a five-port silicon optical switch based on the optimized Spanke–Beneš structure for 2-D-mesh network on chip. We optimize it by substituting optical waveguide crossings for 2 × 2 optical switching units. By this approach, the total number of optical switching units is reduced from 10 to 8 compared to a five-port optical switch based on Spanke–Beneš structure. The 2 × 2 optical switching unit is based on balanced Mach–Zehnder interferometers with integrated titanium nitride microheaters on both arms. The average operating power consumption of the whole switch is 215 or 178 mW for the left arm or right arm by using single-arm driving, which will be reduced to 89 mW by using dual-arm driving. The insertion losses (excluding coupling losses) of the five optical links under “all-cross” and “all-bar” states are 3.2–6.0 and 3.3–6.2 dB, respectively, in the wavelength range of 1525–1565 nm. The optical signal-to-noise ratios are larger than 12.2 dB in 1525–1565 nm. 40-Gb/s data transmission experiment is implemented to verify the transmission functionality. The 10–90% rising and 90–10% falling time of the optical switching units in the device by thermal tuning are all ∼17 μs.